2023
DOI: 10.1007/s13132-023-01202-2
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Innovation and Absorptive Capacity as an Antecedent on IT Firm Financial Performance

Abstract: A lack of collaborative innovation and absorptive capacity in firms causes projects to fail. Managers/employees in small and medium enterprises (SMEs) are not sufficiently aware of the practices of intellectual capital and nor do they collect, share, transfer, and utilize knowledge properly. This current study, therefore, focuses on the relationship between collaborative innovation and the financial performance of Portuguese IT sector SMEs, with a mediating role of absorptive capacity and a moderating role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…The findings obtained corroborate the results of other investigations such as Choi and Park (2017), Mata et al (2023) and Senivongse et al (2019) who demonstrated that absorptive capability has a direct influence on financial performance. On the other hand, they contradict the results of the research carried out by Kale et al (2019) who demonstrated that the dimensions of Acquisition and Use of knowledge, which are part of the Absorptive capability, have a positive and significant relationship with nonfinancial performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings obtained corroborate the results of other investigations such as Choi and Park (2017), Mata et al (2023) and Senivongse et al (2019) who demonstrated that absorptive capability has a direct influence on financial performance. On the other hand, they contradict the results of the research carried out by Kale et al (2019) who demonstrated that the dimensions of Acquisition and Use of knowledge, which are part of the Absorptive capability, have a positive and significant relationship with nonfinancial performance.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that homogeneous absorption positively influences shortterm financial performance, while heterogeneous absorption does so negatively. Mata et al (2023) in a study carried out on 308 managers and employee from IT companies, demonstrated that absorptive capacity has a direct influence on financial performance, in addition, it has a mediating effect between collaborative innovation and financial performance. Likewise, Senivongse et al (2019) demonstrated that the absorption capacity in a highly dynamic market such as that of SMEs that offer technology services, has a direct and positive impact on the financial performance of the company.…”
Section: Absorptive Capacity and Financial And Non-financial Performancementioning
confidence: 99%